(untitled) (International journal of artificial intelligence, 2026)
Engineering graphics is a branch of geometry that studies methods for depicting spatial shapes in a drawing and algorithms for solving positional, metric, and constructive problems. The main purpose of studying engineering graphics is for students to acquire the knowledge and skills necessary to execute and read drawings, compile design documentation, and make sketches of structures and parts. Tasks for comparing objects, images, and concepts are widely used in psychological research, as well as in teaching logic. In this case, the support goes to the analysis of the basis for comparison.